Eficiencia de las sociedades musicales de la Comunidad Valenciana - Pau Rausell Koster; Vicente Coll-Serrano; Raúl Abeledo Sanchis; Francisco Marco-Serrano (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2013)
– Empirical applications for assessing the efficiency in cultural organizations are still scarce. In this paper, we use a non-radial, output-oriented, DEA model for assessing the efficiency of a sample of 292 Musical Societies in the Valencian Community. The interest in this type of cultural organization lies in both its socio-economic relevance and its degree of territoriality. The achieved results show that the average efficiency of the Musical Societies stands at 72.66% and points out to the existence of certain specificities in the supply and demand for provincial markets in which they operate.
Keywords: C14; D24; L82; Z10; 330; efficiency; DEA; musical societies